Religion, Populism and Politics: The Notion of Religion in Election Manifestos of Populist and Nationalist Parties in Germany and The Netherlands - Leon van den Broeke; Katharina Kunter (Religions, 2021)
This article is about the way that the notion of religion is understood and used in election manifestos of populist and nationalist right-wing political parties in Germany and the Netherlands between 2002 and 2021. In order to pursue such enquiry, a discourse on the nature of manifestos of political parties in general and election manifestos specifically is required. Election manifestos are important socio-scientific and historical sources. The central question that this article poses is how the notion of religion is included in the election manifestos of three Dutch (LPF, PVV, and FvD) and one German (AfD) populist and nationalist parties, and what this inclusion reveals about the connection between religion and populist parties. Religious keywords in the election manifestos of said political parties are researched and discussed. It leads to the conclusion that the notion of religion is not central to these political parties, unless it is framed as a stand against Islam. Therefore, these parties defend the Jewish-Christian-humanistic nature of the country encompassing the separation of ‘church’ or faith community and state, the care for the historical and cultural heritage of church buildings, and the subordination of the freedom of religion to the freedom of expression. The election manifestos also reveal that Buddhism and Hinduism are absent in the discourses of these political parties.